Risks of De-institutionalizing Foreign Policy in Nepal - Ray, Kaushal Kishor (NPRC Journal of Multidisciplinary Research, 2026)
Background: In an increasingly complex international environment, the effective execution of foreign policy is crucial for safeguarding national interests and enhancing a country’s image and dignity. Institutions, with their established rules, norms, and organizational structures, are fundamental to ensuring policy stability, coherence, and continuity in this process. Objective: This article examines the growing trend of de-institutionalizing foreign policy in Nepal, where formal diplomatic processes are increasingly bypassed in favor of informal, ad-hoc, and leader-centric approaches. It analyzes the causes, challenges, and risks associated with this trend. Methods: The study employs a qualitative analytical approach, drawing on theoretical frameworks of institutionalism and foreign policy analysis. It synthesizes findings from academic literature, case studies of other nations (e.g., Mexico), official reports, and contemporary Nepali political and diplomatic examples to substantiate its arguments. Findings: The analysis identifies globalization, the rapid advancement of information technology, the democratization of foreign policy, and domestic political instability as primary drivers of de-institutionalization in Nepal. This trend has led to critical challenges, including poor inter-agency coordination, fragmented policy positions in international negotiations, weakened accountability, and suboptimal outcomes in areas like climate diplomacy and international development cooperation. Conclusion: De-institutionalizing foreign policy poses significant risks in its effective implementation and achieving its objectives of protecting and promoting national interests. Reversing this trend through enhanced institutionalization, capacity-building within the Ministry of Foreign Affairs, and strengthening established rules and coordinating mechanisms is essential for the effective implementation of foreign policy ensuring its continuity, credibility, and efficacy. Novelty: This article provides a specific and timely analysis of de-institutionalization within Nepal’s foreign policy landscape, a subject rarely examined systematically. It connects global drivers of this phenomenon to Nepal’s unique context of political instability and institutional capacity constraints.